Cisplatin Tumor Biodistribution and Efficacy after Intratumoral Injection of a Biodegradable Extended Release Implant. (19th January 2011) - Shikanov, Ariella; Shikanov, Sergey; Vaisman, Boris; Golenser, Jacob; Domb, Abraham J.
Abstract : Local delivery of chemotherapeutic drugs has long been recognized as a potential method for reaching high drug doses at the target site while minimizing systemic exposure. Cisplatin is one of the most effective chemotherapeutic agents for the treatment of various tumors; however, its systemic toxicity remains the primary dose-limiting factor. Here we report that incorporation of cisplatin into a fatty acid-based polymer carrier followed by a local injection into the solid tumor resulted in a successful tumor growth inhibition in heterotopic mouse bladder tumor model in mice. Platinum concentration in the tumor tissue surrounding the injected implant remained above the therapeutic level up to 14 days after the injection, while the plasma levels were several orders of magnitude lower comparing to systemic delivery. The reported delivery system increased the maximum tolerated dose of cisplatin 5 times compared to systemic delivery, thus potentially improving antitumor efficacy of cisplatin in solid tumor model.